Spontaneous Thrombosis of Dural Arteriovenous Malformation: A Case Report - M, Sobri; WZ, Mezlina; JH, Subramaniam (IIUM Medical Journal Malaysia, 2009)
Dural arteriovenous malformation (DAVM) is relatively rare and defined as abnormal connections or shunts between the arterial and the venous side of vascular tree located within the dura mater. Spontaneous closures of DAVM are rare and have been scarcely reported. This case report will describe the neuroimaging findings and classification of DAVM. A 50 year old lady presented with headache. Neuroimaging showed prominent serpinginous flow-void structures, cerebral angiogram confirmed the presence of DAVM at the occipital region. She had defaulted treatment and follow up for 3 years. On second admission, she had a cerebral angiogram which showed normal findings with no evidence of fistulas or malformation. She was discharged well. Causes of spontaneous closure of DAVM are discussed.